Post-extractive juridification: Undoing the legal foundations of mining in El Salvador. Issue 138 (January 2023) - Montoya, Ainhoa
Highlights: Explains El Salvador's unique mining ban and examines how transformative it has been. Ethnographically explores citizen-led lawmaking to facilitate a mining-free future. Discusses the limits of countering neoliberal statecraft without simultaneously decolonising law. Abstract: In 2017 El Salvador passed the world's first and only blanket ban on metal mining. This article explores this unique exception to the neoextractive path followed by much of Latin America since the early 2000s—an exception brought about by citizen-led lawmaking processes. Drawing from fieldwork research in El Salvador, I suggest that the ban was enabled not so much by a negative assessment of extraction-led development as by multiple other factors, including short-term electoral expediencies; the shared genealogy and history of grassroots opposed to mining and left-wing governments; the ongoing convergence of nationwide anti-mining movements supported by the Catholic Church; and a lack of vested interests in the mining industry on the part of local elites. Indeed, a few years on from the ban, successive governments have not fulfilled their obligation to eradicate mining, with many activists fearing an eventual repeal. Crucially, citizen-led lawmaking aimed at undoing the neoliberal ethos of the legal architecture that has facilitated mining throughout much of Latin America has failed to address the colonial legacies of this architecture. Overall, the article argues that mining-free futures require comprehensive lawmaking endeavours that include both legislative challenges to neoliberal statecraft and a comprehensive overhaul and decolonization of the legal foundations of mining.